Specifics of family relations and emotional relationships in families of the women with paranoid schizophrenia - M. Driuchenko (Journal of Education, Health and Sport, 2016)
Driuchenko M. Specifics of family relations and emotional relationships in families of the women with paranoid schizophrenia. Journal of Education, Health and Sport. 2016;6(10):810-820. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.265724